Price discovery issues for fed cattle - Mintert, J.; Ward, C.E.; Peel, D.S.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Interviews were conducted with cattle feeders, beef packers, and others involved in the beef industry to discern their concerns about fed-cattle price discovery. Three issues predominated. First was the need to better identify beef quality, ideally by objective means. Quality often, but not always, referred to tenderness and the “eating experience” of consumers. Second was the need for greater pricing accuracy, signaling a desire for less average pricing and more value-based pricing. The need for improved market information was the third issue identified.
Keywords: Beef; Fed cattle price; Price discovery